A comparison between active drag in front-crawl and passive drag on the body with a streamlined position at various velocities - Narita, K.; Nakashima, M.; Sengoku, Y.; Homma, M.; Tsubakimoto, S.; Takagi, H. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
The purpose of this study was to compare active drag during front-crawl swimming performed by competitive swimmers with passive drag acting on the same group of swimmers with a streamlined position at various velocities. Seven male competitive swimmers participated in this study, and the testing was conducted in a swimming flume. Active drag was evaluated for front-crawl swimming with upper and lower limb motion using a methodology that estimates the drag in swimming using measured residual thrust values (MRT method). Passive drag was measured by a load cell connected to the swimmers with a streamlined position using a stainless-steel wire. In each case, drag was estimated at six staged velocities ranging from 1.0 to 1.5 m/s. To compare the drags at various velocities, we calculated coefficients a and b by applying the measured force value at each velocity to the equation D = a vb (D: drag, v: velocity). The active drag estimated from the MRT method (a = 35.7 ± 5.3, b = 2.80 ± 0.22) was larger than passive drag (a = 23.6 ± 3.1, b = 2.08 ± 0.23). Furthermore, the difference between active and passive drag was large at high velocities. Therefore, it is possible that the effects of factors other than posture and/or body shape have a large influence on active drag, especially at high velocity.